A beginner's guide to integrating multi-omics data from microbial communities. (30th June 2022) - Heintz-Buschart, Anna; Westerhuis, Johan A.
Abstract : Microbial communities are immensely important and occur nearly everywhere, but their inner workings are still being discovered. The early years of microbiome research have been dominated by cataloguing the sheer diversity of microbes in these communities. Now, more and more studies try to understand connections between the microbes, between the way communities are built and how they function, and between their activity and the effects on their surroundings, including host organisms like humans. Omics measurements, or meta-omics as they are called when multiple organisms are measured at the same time, are a cornerstone in this endeavour. Here, we will discuss why their integration is important, how it can be achieved, what pitfalls may be avoided and which approaches are taken by integrative studies.